Mesenchymal stem cells in a transgenic mouse model of multiple system atrophy: immunomodulation and neuroprotection. - Sylvia Stemberger; Angelika Jamnig; Nadia Stefanova; Günter Lepperdinger; Markus Reindl; Gregor K Wenning (PLoS ONE, 2011)
Mesenchymal stem cells (MSC) are currently strong candidates for cell-based therapies. They are well known for their differentiation potential and immunoregulatory properties and have been proven to be potentially effective in the treatment of a large variety of diseases, including neurodegenerative disorders. Currently there is no treatment that provides consistent long-term benefits for patients with multiple system atrophy (MSA), a fatal late onset α-synucleinopathy. Principally neuroprotective or regenerative strategies, including cell-based therapies, represent a powerful approach for treating MSA. In this study we investigated the efficacy of intravenously applied MSCs in terms of behavioural improvement, neuroprotection and modulation of neuroinflammation in the (PLP)-αsynuclein (αSYN) MSA model.MSCs were intravenously applied in aged (PLP)-αSYN transgenic mice. Behavioural analyses, defining fine motor coordination and balance capabilities as well as stride length analysis, were performed to measure behavioural outcome. Neuroprotection was assessed by quantifying TH neurons in the substantia nigra pars compacta (SNc). MSC treatment on neuroinflammation was analysed by cytokine measurements (IL-1α, IL-2, IL-4, IL-5, IL-6, IL-10, IL-17, GM-CSF, INFγ, MCP-1, TGF-β1, TNF-α) in brain lysates together with immunohistochemistry for T-cells and microglia. Four weeks post MSC treatment we observed neuroprotection in the SNc, as well as downregulation of cytokines involved in neuroinflammation. However, there was no behavioural improvement after MSC application.To our knowledge this is the first experimental approach of MSC treatment in a transgenic MSA mouse model. Our data suggest that intravenously infused MSCs have a potent effect on immunomodulation and neuroprotection. Our data warrant further studies to elucidate the efficacy of systemically administered MSCs in transgenic MSA models.